Influência de fatores externos e internos sobre o deslocamento de guildas da herpetofauna - Silva, Marcela Fernandes Vilela (2013)
Internal (motivation, physiology) and external (physical environment) variables could affect an organisms displacement capacity. Few studies about vertebrate movement include internal factors, and those about herpetofauna are even fewer. Some researches minimize the importance of external factors and many of them also neglect individual variation, because they emphasize just the population mean. The aim of this work was to verify whether there is a relationship between internal (sex and biomass) and external (landscape and climatic parameters) factors on one hand and daily displacement of the amphibians Rhinella ornata and Proceratophrys boiei, and the lizard Enyalius perditus, and also among these species. Daily home range of the amphibians was also compared to literature data on a marsupial with similar biomass. Internal and external factors did not explain displacement of species when considered in isolation. When these species were clustered in guilds, forest specialists (P. boiei plus E. perditus) and generalists (R. ornata), there was a positive relationship between displacement and fragments proximity, and also with maximum temperature in the first group. However, there was no difference of displacement between both guilds. Between species, E. perditushad the larger daily displacement followed by R. ornata and finally by P. boiei. Regarding home range, the descendent order was: marsupial, followed by R. ornata and finally by P. boiei. These results reinforced the importance of the variation within and between species, overcoming the influence of external or internal factors.